Espectro trófico de la tilapia Oreochromis aureus (Perciformes: Cichlidae) en la presa Infiernillo, Michoacán-Guerrero, México - Jiménez-Badillo, María de Lourdes; Nepita-Villanueva, Marta Rocío (Revista de Biología Tropical, 2000)
The tropbic spectrum of tilapia Oreochromis aureus (Steindachner 1864), was deterrnined by stomach content analysis in 153 organisros collected during 1993 in Michoacán-Guerrero, México. The feeding status of the fish at the time of observation was evaluated by the examination of fat surrounding the gut, gastric replection and the condition coefficient. The quantitative evaluation of the food items was carried out by the combination of the following analysis: Frequency of Occurrence, Volurnetric Method, Volumetric Mean Index and Relative Importilnce Index. Diet consisted of: detritus and vascular plat residues as a primary food; unicellular algae as' secondary food; and remains of insects and fish, graminean seeds, fiJamentous algae, cJadocerans, ostracods, rotifers and copepods as occasional food. Wedetected a difference in food preferences between juveniles and adults and a variation in the consurnption proportíons of some food iteros duringtbe rainy and dry seasons. Thus, we concluded that O. aureus is an omnivorous species with prefeJ;'eAce for detritus<¡md vascular plant remain. Feeding seems to be, deterrnin